Industrial structure upgrading, urbanization and urban-rural income disparity: evidence from China. Issue 15 (2nd September 2021) - Hong, Mingyong; Zhang, Wenjie
ABSTRACT: This study examines the influence of industrial structure upgrading in China on urban-rural income disparity. Using panel data from 30 provinces with the empirical analysis methodology, we find that, during 2013 and 2018, industrial structure upgrading in China plays a significantly positive role in narrowing urban-rural income disparity. By the mechanism analysis, we find that urbanization rate is an intermediary variable which affects this causation. Further, urbanization in industrial structure upgrading for the influence of narrowing rural-urban income disparity existing in threshold effects, and threshold levels present a regional difference. Using the urban-rural consumption gap as the proxy variable of income gap, the result is still stable.